2008
DOI: 10.1038/gene.2008.3
|View full text |Cite
|
Sign up to set email alerts
|

A population-specific diabetogenic haplotype HLA-A2,Cw1,B56,DR4,DQ8 is associated with high birthweight in Finnish diabetic families

Abstract: Children with type 1 diabetes (T1D) susceptibility HLA genotypes are shown to have an increased birthweight. We investigated to what extent T1D-predisposing HLA haplotypes were associated with increased birthweight. A total of 1255 Finnish children comprising those with T1D and their non-diabetic siblings were investigated. A total of 342 children and their non-diabetic parents were HLA genotyped. Birthweight data were obtained from the national Medical Birth Registry. The population-specific diabetogenic hapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…While there are some data suggesting that birthweight differs according to HLA genotype, including increased birthweight in children with certain type 1 diabetes-susceptibility HLA alleles [9][10][11], there is no clear relationship between birthweight and risk of type 1 diabetes [12,13]. Moreover, in our BABYDIAB study, the highest risks for autoimmunity appeared to be associated with normal birthweight [23].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…While there are some data suggesting that birthweight differs according to HLA genotype, including increased birthweight in children with certain type 1 diabetes-susceptibility HLA alleles [9][10][11], there is no clear relationship between birthweight and risk of type 1 diabetes [12,13]. Moreover, in our BABYDIAB study, the highest risks for autoimmunity appeared to be associated with normal birthweight [23].…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, a causal aetiological role for insulin sensitivity in driving beta cell destruction, or indeed, initiating islet autoimmunity, has been suggested, but no direct evidence has been reported. Indirect evidence for this comes from reports showing that HLA genotypes associated with a high risk for type 1 diabetes are linked with birthweight, and from epidemiological studies indicating that the incidences of obesity and type 1 diabetes are increasing in parallel in childhood [9][10][11][12][13]. Stronger evidence would be provided if insulin demand was found to be increased in the prediabetic period, but thus far no direct comparison of insulin sensitivity between autoantibody-positive and -negative individuals has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The type 1 diabetes high-risk HLA genotypes have shown an association with higher birth weight in the general population in Sweden 12 and Finland. 11 Nevertheless, the same genotypes have shown a relation to lower birth weight in Norway. 16 To be a carrier of any of these four genotypes was the criteria for the enrollment of newborn babies into the Environmental determinants of Diabetes in the Young (TEDDY) study.…”
Section: Introductionmentioning
confidence: 99%
“…8 Some studies have indicated that the human leukocyte antigen (HLA) system on chromosome 6 may act on birth size. 9, 10, 11, 12 The HLA system contributes about 50% of the risk for sib-pairs to develop type 1 diabetes. 13, 14 The HLA genotypes conferring the highest risk in the general Caucasian population are limited to the DR3-DQA1 * 0501-DQB1 * 0201/DR4-DQA1 * 0301-DQB1 * 0302; DR4-DQA1 * 0301-DQB1 * 0302/DR4-DQA1 * 0301-DQB1 * 0302; DR8-DQA1 * 0401-DQB1 * 0402/DR4-DQA1 * 0301-DQB1 * 0302 and DR3-DQA1 * 0501-DQB1 * 0201/DR3-DQA1 * 0501-DQB1 * 0201 genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…There have been also other studies looking for possible associations between HLA‐risk group and birth weight . Järvinen et al .…”
Section: Discussionmentioning
confidence: 99%